Physical Activity and the Quality of Life of Elderly Patients with Hypertension - Sri Jumaiyah; Kurnia Rachmawati; Hasby Pri Choiruna (University of Muhammadiyah Malang, 2020)
Introduction: Hypertension is a degenerative disease that causes changes in the elderly so it will affect the quality of life of the elderly. One effort to improve the health status and quality of life of the elderly is maintaining health conditions with activities. Objective: The purpose of this study was to determine the relationship of physical activity and the quality of life of elderly patients with hypertension in the working area of the Hambawang Beach Health Center. Method: This study used correlation with the cross sectional design approach. Respondents numbered 56 elderly taken in total sampling. The research instruments were PASE questionnaire and WHOQOL-BREF questionnaire. Data analysis used chi square test. Results:There was a relationship of physical activity with the quality of life of elderly people with hypertension (p = 0,000). Odds Ratio value of 49,5 means that elderly who have less physical activity are 49,5 times more likely to have a poor quality of life of the elderly compared to good physical activity of the elderly. Discussion: Good physical activity can improve the quality of life of the elderly. It was recommended to the elderly to do physical activities such as walking and doing sports.